Loes Schenk-Sandbergen (ed). Women and Seasonal Labour Migration. (Indo-Dutch Studies on Development Alternatives-(16). New Delhi: Sage Publications. 1995. 345 pages. Hardback. Indian Rs 375.00. Paperback. Indian Rs 200.00. (The Pakistan Development Review, 1996)
So far migrants who are poor, and particularly the increasing number of women who migrate for survival, have not been given much attention. In the literature, women are considered to be 'tied movers'. This book has engendered the important issue of seasonal, survival migration. This volume, No. 16, in the series on Indo-Dutch series on Development Alternatives, consists of four studies and focuses on women who stay behind while males migrate, and on women who migrate individually or with the family. The crucial question asked is: "Is the consequence of women and men migration subordination or emancipation of women?"